2009
DOI: 10.1128/aem.01389-08
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-Derived Clones Encoding Two Novel Lactonase Family Proteins Involved in Biofilm Inhibition in Pseudomonas aeruginosa

Abstract: Here we report the isolation and characterization of three metagenome-derived clones that interfere with bacterial quorum sensing and degrade N-(3-oxooctanoyl)-L-homoserine lactone (3-oxo-C 8 -HSL). By using a traI-lacZ gene fusion, the metagenome-derived clones were identified from a soil DNA library and analyzed. The open reading frames linked to the 3-oxo-C 8 -HSL-degrading activities were designated bpiB01, bpiB04, and bpiB07. While the BpiB07 protein was similar to a known lactonase, no significant simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 54 publications
2
80
0
Order By: Relevance
“…Metagenomic analyses faciliated the discovery of QlcA, BipB01, BipB04, BipB05, and BipB07 (68,74,75), and screens for AHL-degrading bacteria led to the identification of QsdA of Rhodococcus erythropolis strain W2 (70), AiiM of Microbacterium testaceum (71), AidH of Ochrobactrium sp. strain T63 (72), and QsdH of Pseudoalteromonas byunsanensis strain 1A01261 (73).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…Metagenomic analyses faciliated the discovery of QlcA, BipB01, BipB04, BipB05, and BipB07 (68,74,75), and screens for AHL-degrading bacteria led to the identification of QsdA of Rhodococcus erythropolis strain W2 (70), AiiM of Microbacterium testaceum (71), AidH of Ochrobactrium sp. strain T63 (72), and QsdH of Pseudoalteromonas byunsanensis strain 1A01261 (73).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…240B1 (4), AttM (9.9% identity) from A. tumefaciens C58 (34), AhlD (11.7% identity) from Arthrobacter sp. IBN110 (23), QsdA (12.5% identity) from R. erythropolis W2 (30), and QlcA (14.9% identity), BpiB01 (12.9% identity), BpiB04 (13.3% identity), and BpiB07 (12.4% identity) from the soil metagenome (24,27). A conserved HXHXDH sequence is a zinc-binding motif that is found in the metallo-␤-lactamase superfamily and is common to many AHL lactonase enzymes (5).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Human and murine paraoxonase degrades AHL by hydrolyzing its lactone ring (21). Novel AHL lactonase genes have been isolated from a metagenomic library which was constructed from environmental soil samples (24,27). AHL-degrading genes have also been utilized in the biocontrol of plant diseases.…”
mentioning
confidence: 99%
“…Genes encoding AHL-acylase, which hydrolyzes the amide bond of AHL, have been cloned from Ralstonia spp., Anabaena spp., Streptomyces spp., Shewanella spp., and Pseudomonas aeruginosa. Novel AHLdegrading genes have been isolated from metagenomic libraries constructed from soil samples (19,22). Recently, it was reported that some members of the α/β hydrolase family have AHL-lactonase activity (11,30).…”
mentioning
confidence: 99%